Определение параметров основного колебательного состояния молекулы 28SiH4 - Распопова Н. И. Наталья Ивановна; Громова О. В. Ольга Васильевна; Бехтерева Е. С. Елена Сергеевна; Бауэреккер З. Зигурд (2017, 2017)
Заглавие с экрана